Marketing effectiveness and accountability in SMEs a multimethological approach - Smith, Trevor A. 1958- (Cham Springer International Publishing AG, 2022)
This book sheds light on marketing effectiveness and accountability marketing in small and medium-sized enterprises (SMEs). Using a multi-method investigation, it includes a knowledge inquiry of marketing knowledge and customer knowledge, a qualitative inquiry utilizing semi structured interviews and thematic data analysis, a quantitative analysis utilizing survey and structural equations modelling, and a case study that employs both narrative (storytelling) data analysis and an accountability audit with a techno marketing SME. SMEs generally face financial constraints that limit their ability to carry out the marketing function. Addressing this limitation, the author presents conceptual models based on the resource based view and the knowledge based view to show how marketing capabilities can lead to performance improvement in the SMEs. The lessons learnt provide guidance in the practice of marketing for small and medium firms to be more effective in their marketing investments and make wiser marketing decisions. This book will prove useful for both researchers and practitioners by extending knowledge on marketing performance management in the SMEs. Trevor A. Smith is Senior Lecturer in Marketing and Methodology at Mona School of Business and Management in the University of the West Indies, Jamaica. His research focuses on marketing and consumer psychology. -- Provided by Publisher.
Introduction to Marketing Effectiveness and the SMEs -- Marketing Effectiveness and Accountability with Implications and Applications for SMEs -- Knowledge and Marketing Effectiveness with Implications and Applications for SMEs -- A Qualitative Inquiry into Marketing Effectiveness of the SMEs -- The Key Drivers of Marketing Efficiency of the SME and the Digital Link to SME Performance -- The Case of Marketing Effectiveness in a Successful SME: Point Global Marketing Limited -- Synopsis and lessons learnt on marketing effectiveness and accountability of the SMEs -- Conclusion
Keywords: Small business marketing